Construction and validation of the TESL foundation entrance test in a public university / Geethanjali Narayanan - Geethanjali , Narayanan (2018)
In the 2015 Global Monitoring Report, there is a large disparity in the pupil-teacher ratios across the globe. However, to address this issue, the quality of the recruitment of teachers should not be brushed off. Teachers must be well versed in their subject matter to make them authoritative and credible. The development of a highly qualified and committed teaching force is one of the main concerns of the global educational reform. As such the aim of this study was to construct and validate an English Language entrance test (ATET) for the TESL foundation programme in a public university, so that the graduating students from this programme will be highly sought after at the TESL degree level, making them more knowledgeable and authoritative in their field. The ATET was developed and validated over 4 years, 2010-2013, to determine the items have psychometric properties. The construction and validation of ATET employed the framework that maps the Rasch Model and Kane‟s Validity Argument. Winsteps was used to analyse the bulk of the quantitative data which showed fit and order validity. The final outcome, after three sequentially improvised versions, was ATETv3 with 60 MCQ items, testing Reading, Grammar and Writing skills and one essay question (open-ended). These items range in difficulty between -3.24 and 4.38 logits, with Person Reliability of 0.86 and Item Reliability of 0.98 and Cronbach Alpha, 0.8. The essay component was analysed using Facets as well as EduG and the D-Study (Decision Study) suggested one rater (an experienced one) is sufficient, with a G-coefficient of 0.91. Meanwhile this study also established Predictive (r=0.85) and Construct (r=0.78) validity using SPSS. On the whole the cut-off point to be accepted into the programme was set at -1 logit. The paper-pencil ATET, which was originally meant to select appropriate candidates for the TESL foundation programme, is currently adopted as a digitized diagnostic test, conducted online in a public university.